Curricular Development and Implementation of a Longitudinal Integrative Medicine Education Experience for Trainees and Health-Care Professionals at an Academic Medical Center - Susanne M Cutshall APRN, CNS, DNP; Tejinder K Khalsa MD; Tony Y Chon MD; Sairey M Vitek MBA; Stephanie D Clark PhD; Debra L Blomberg MBA; Rafid Mustafa MD; Anjali Bhagra MD (SAGE Publishing, 2019)
A growing number of patients and consumers are seeking integrative medicine (IM) approaches as a result of increasing complex medical needs and a greater emphasis on prevention and health promotion. Health-care professionals need to have knowledge of the evidence-based IM resources that are safe and available to patients. Medical institutions have acknowledged the need for education and training in various IM modalities and whole-health approaches in medical curricula. There is a strong need to develop and incorporate well-structured IM curricula across all levels of learning and practice within medicine. This article provides an example of the development, implementation, impact, and assessment of IM education curricula across all learner levels at a large academic medical center.